2014
DOI: 10.1111/eci.12383
|View full text |Cite
|
Sign up to set email alerts
|

Bed rest does not induce hypercoagulability

Abstract: Our data indicate that the re-ambulation period is associated with a tendency towards hypercoagulability: ttPeak and StartTail were significantly shorter, Peak and VELINDEX were significantly higher compared to baseline. Moreover, plasma levels of F1 + 2, TAT, FVII and FVIII were significantly higher compared to baseline. The results from our study suggest that bed rest by itself is not associated with hypercoagulable states in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 24 publications
3
38
0
Order By: Relevance
“…Prolonged bed rest in healthy volunteers does not induce a hypercoagulability state [40], however this is not generalizable to the perioperative context and caution should be advised if prolonged immobilization is required post-surgery.…”
Section: Perioperative Management Of Doacsmentioning
confidence: 99%
“…Prolonged bed rest in healthy volunteers does not induce a hypercoagulability state [40], however this is not generalizable to the perioperative context and caution should be advised if prolonged immobilization is required post-surgery.…”
Section: Perioperative Management Of Doacsmentioning
confidence: 99%
“…Bedrest immobilization is routinely used to simulate physiological deconditioning including that of the cardiovascular system (see [11]). Whilst adrenomedullin and galanin have been investigated with regard to acute orthostatic intolerance, their potential role in the reduced orthostatic intolerance following bed rest has yet to be determined.…”
mentioning
confidence: 99%
“…X [92] Our data indicate that the re-ambulation period is associated with a tendency towards hypercoagulability.…”
Section: Appendix Statements Made In the Conclusion Of The Abstract mentioning
confidence: 68%
“…In the original article, we reported that bedrest by itself is not associated with hypercoagulable states in healthy subjects [92].…”
Section: Involvement Of Leucocyte/endothelial Cell Interactions In Anmentioning
confidence: 97%